Traffic radar performance analysis via visualization - Kumaraganesh Anthony Sagayanathan. (2010)
The aim of this project is to achieve the objectives that was given and set out initially, to develop an animator tool for 24/7 traffic radar surveillance application. With the development of a fully functional Win32 application along with the 3D animation engine, the options for future enhancements have greatly increased. Vehicle modeling is proposed for real-time traffic simulation in 3-Dimensional virtual environments. In our approach, a traffic flow is comprised of autonomous virtual agents/vehicles, each of which has its own behavior characteristic. Traffic simulation is the result of the collective behavior of every virtual agent, which similarly to the reality, is affected by the factors concerning the design and condition of roads, traffic control, and the movement of other nearby vehicles. The system is capable of handling a large number of vehicles in a large complex environment for traffic simulation and training. The successful development of this program would enable the user to visualize the exact scene of traffic flow at a particular location of an expressway. In the event of bad weather conditions or visibility deficiency, traffic cameras might not serve their purpose of conveying visual data to the public. During such instances, this method will involve simulation of traffic flow in a 3-Dimensional environment using the extrapolation of the velocity detected by radar and subsequently inputting into the program. The feasibility testing of software to be used concluded with using Autodesk’s 3DStudio Max for the models and OpenGL for the programming of the environment. The visualization program was to be developed in the way of how the viewer would actually view it in the actual scenario. Simulated scenes were developed using Graphical User Interface in a Visual Basic environment where they were then compared with videos of the actual experiment. Further development on entering user inputs will enable the project to be more useful in real time operations.